Efficacy of metacognitive training for patients with borderline personality disorder: Preliminary results. (April 2018) - Schilling, Lisa; Moritz, Steffen; Kriston, Levente; Krieger, Maria; Nagel, Matthias
Abstract: 'Metacognitive training for borderline personality disorder' (B-MCT) represents a complementary group intervention. It aims at raising awareness for cognitive biases that may play an important role in the development and maintenance of borderline symptomatology. For the present study, we evaluated the effectiveness of this new approach against a control condition. Seventy-four inpatients with borderline personality disorder (BPD) were randomly assigned to metacognitive training for BPD or progressive muscle relaxation training as an add-on intervention to treatment as usual. Severity of symptomatology was assessed at baseline, four weeks after beginning and six months after completion of the intervention. The per-protocol and intention-to-treat analyses revealed that patients in the metacognitive training group showed significantly greater reductions on the primary outcome ( Borderline Symptom List-23) after six months. Progressive muscle relaxation was superior in alleviating depressive symptoms (secondary outcome : Beck Depression Inventory) at the long-term follow-up. Findings provide preliminary evidence that metacognitive training for BPD yields surplus effects to standard treatment. Highlights: We evaluated efficacy of metacognitive training for borderline personality disorder. 74 patients were randomised to metacognitive training (MCT) or a progressive muscle relaxation group. MCT yielded significant surplus effects to standard treatment after six months.